2018
DOI: 10.1007/s11663-018-1196-9
|View full text |Cite
|
Sign up to set email alerts
|

A New Experimental Design to Study the Kinetics of Solid Dissolution into Liquids at Elevated Temperature

Abstract: A new method was developed to study the dissolution of a solid cylinder in a liquid under forced convection at elevated temperature. In the new design, a rotating cylinder was placed concentrically in a crucible fabricated by boring four holes into a blank material for creating an internal volume with a quatrefoil profile. A strong flow in the radial direction in the liquid was created, which was evidently shown by computational fluid dynamic (CFD) calculations and experiments at both room temperature and elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Carbonless bricks 1 1 Electric energy consumption not considered because of negligible differences in the comparison between the manufacturing processes of the two types of bricks; 2,3 Considered undifferentiated as Toluene, 2-chloro; 4 Considered half as para-Xylene and half as m-Xylene; 5 Not present alone in the Ecoinvent ® database version 3.4 and considered equivalent to "BTEX" (Benzene, Toluene, Ethylbenzene, and Xylene) in unspecified ratio; 6,7,8 In the Ecoinvent ® database called "Cumene", "1-Propyl Benzene" and "T-butylbenzene", respectively; 9 Not present in the Ecoinvent ® database version 3.4 and not included in the LCI.…”
Section: Output Wanted [T]mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonless bricks 1 1 Electric energy consumption not considered because of negligible differences in the comparison between the manufacturing processes of the two types of bricks; 2,3 Considered undifferentiated as Toluene, 2-chloro; 4 Considered half as para-Xylene and half as m-Xylene; 5 Not present alone in the Ecoinvent ® database version 3.4 and considered equivalent to "BTEX" (Benzene, Toluene, Ethylbenzene, and Xylene) in unspecified ratio; 6,7,8 In the Ecoinvent ® database called "Cumene", "1-Propyl Benzene" and "T-butylbenzene", respectively; 9 Not present in the Ecoinvent ® database version 3.4 and not included in the LCI.…”
Section: Output Wanted [T]mentioning
confidence: 99%
“…From the previous discussion it is derived that refractory materials are identifiable as one of the major sources of non-metallic inclusions in the molten steel during ladle metallurgy. Therefore, drawing up carbon free bricks for ladle furnaces is a significant contribution leading to build UCS [7]. The EU funded the research project LeanStory, aiming to promote such new line of refractories through the cooperation between industrial partners and scholars, where different recipes have been elaborated (see Section 2).…”
Section: Introductionmentioning
confidence: 99%
“…The CFD study helps to determine the shear stresses on the rotating refractory finger to properly replicate the wear conditions in the up-scaled process. Work by Wang et al [19] found that the dissolution rate of cylindrical rotating refractory fingers is mostly independent of the rotation speed, due to low radial velocity of the flow. However, shear stresses on the rectangular-shaped refractory finger used in the present study are expected to be dependent on the rotational speed.…”
Section: Introductionmentioning
confidence: 99%